1961
DOI: 10.1139/b61-073
|View full text |Cite
|
Sign up to set email alerts
|

TRANSLOCATION OF C14 IN TOBACCO AT DIFFERENT STAGES OF DEVELOPMENT FOLLOWING ASSIMILATION OF C14O2 BY A SINGLE LEAF

Abstract: Single leaves of tobacco plants at four different stages of development were allowed to carry on photosynthesis in C14O2 for 30 to 50 minutes followed by photosynthesis in air. The total elapsed time from the beginning of assimilation was [Formula: see text] hours. Redistribution of C14 was determined in: I, a young plant with eight leaves; II, an older plant with 19 leaves; III, a mature flowering plant with 29 leaves; IV, a mature seed plant with 35 leaves. The leaf treated with C14O2 in each of the four pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

1962
1962
1997
1997

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…3) adjusted for the increased SLW) following LPI 4.1 may have resulted from the decline in translocation rate in the absence of any apparent decline in SPS activity. Our results are in agreement with those of Shiroya et al (19) who observed decreasing translocation rates and an increased sucrose pool size in older tobacco leaves. Evidence exists for a storage pool of sucrose in leaves that is not directly accessible to translocation (6).…”
supporting
confidence: 94%
“…3) adjusted for the increased SLW) following LPI 4.1 may have resulted from the decline in translocation rate in the absence of any apparent decline in SPS activity. Our results are in agreement with those of Shiroya et al (19) who observed decreasing translocation rates and an increased sucrose pool size in older tobacco leaves. Evidence exists for a storage pool of sucrose in leaves that is not directly accessible to translocation (6).…”
supporting
confidence: 94%
“…This conclusion is supported by the results of translocation studies with many plants in which lower, shaded, old leaves have been found not to import assimilates from upper, younger leaves (Belikov 1958;Shiroya et al 1961;Thrower 1962;Hartt, Kortschak, and Burr 1964). Thus, if the lower, shaded leaves are to survive for any length of time, their respiration rate must be greatly reduced.…”
Section: Discussionmentioning
confidence: 86%
“…There is evidence to support the idea that sucrose is the main form in which carbon compounds are translocated in plants (1,7,8,9). Swanson (10) showed that the ratio of labeled hexoses to labeled sucrose decreased with increasing distance from the fed leaf after assimilation of 14CO-.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy ,uc of 14CO.) were generated and introduced into the chamber as previously described (7). The whole planit was placed under illumination of 30,000 lux for 30 min to allowv the fed leaf to fix 14CO.…”
Section: Methodsmentioning
confidence: 99%